Correlation of Dietary Zinc Intake and Serum Zinc with Thyroid Stimulating Hormone (TSH) and Free Thyroxine (FT4) Levels in Adult Hyperthyroid Patients - Harjantini, Utami; Hanim, Diffah; Dewi, Yulia Lanti Retno; Nurwati, Ida (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Hyperthyroidism is a thyroid disorder caused by increased synthesis and secretion of thyroid hormone by the thyroid gland. Hyperthyroidism is characterized by low thyroid stimulating hormone (TSH) and high free thyroxine (FT4) levels. The prevalence of hyperthyroidism in Indonesia was 0.6% in female and 0.2% in male. Zinc acts as an enzyme cofactor that converts thyroxine into triiodothyronine and it affects TSH synthesis. Adequacy of dietary zinc intake and serum zinc levels in hyperthyroid patients indirectly affects TSH and FT4 hormones. Objective: to analyze the correlation of dietary zinc intake and serum zinc with TSH and FT4 levels in adult hyperthyroid patients. Materials and Methods: This cross sectional study sampling based on inclusion and exclusion criteria which obtained 50 adult hyperthyroid patients at the Clinic of the Magelang Health Research and Development Center. Data of TSH and FT4 levels were measured by the ELISA method, serum zinc was measured with the ICP-MS method, dietary zinc intake’s data was collected using the 24 hour dietary recall and it was analyzed based on the table of Indonesian food composition 2017. Statistical analysis used in this study were spearman correlation and multivariate linear regression with 95% confidence level. Results : Dietary zinc intake did not correlate with both TSH and FT4 levels (p>0.05). Serum zinc had no correlation with TSH level (p>0.05), while serum zinc had a positive correlation with FT4 level (r=0.327; β=0.054; p<0.05). Conclusion: Serum zinc concentrations in adult hyperthyroid patients must be maintained because abnormal zinc status in the body’s metabolism will affect FT4 level. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 341-346